Physicochemical Properties of Demineralized Bone Matrix and Calcium Hydroxide Composites Used as Bone Graft Material - Octarina; Florencia Livia Kurniawan; Firda Amalia Larosa; Olivia Nauli Komala; Meircurius Dwi Condro Surboyo (Crystals)
Vertical bone defects can result in alveolar bone resorption, which may be addressed using composite grafts. A combination of demineralized bone matrix (DBM) and calcium hydroxide (Ca(OH)2) has potential as a bone substitute due to its biological and structural properties. This study aimed to identify the optimal DBM–Ca(OH)2 ratio by evaluating their physicochemical properties relevant to bone regeneration. DBM gel and Ca(OH)2 powder were combined at ratios of 1:1, 2:1, 3:1, and 4:1. The mixtures were freeze-dried, ground, and sieved to create granules. The composites were analyzed in terms of their structural and chemical characteristics, including crystallinity, calcium ion release, functional group composition, particle size, surface morphology, and elemental distribution. Increasing the proportion of DBM reduced crystallinity and calcium ion release while influencing particle size. Among all groups, the 2:1 composite demonstrated the most balanced properties: moderate crystallinity, relatively high calcium release, and favorable particle size. Chemical analyses confirmed the presence and interaction of both organic and inorganic components, while elemental mapping showed a uniform distribution of the key elements essential for bone formation. The DBM–Ca(OH)2 composite at a 2:1 ratio has the most promising physicochemical profile, making it a strong candidate for bone graft applications. However, a limitation of this study is the absence of biological testing. Future research should investigate the in vitro and in vivo performance of this composite in bone regeneration.